Online Monitoring System for Harmonics with Passive Filter on A 110 KW Three-Phase Inverter - Mardha Haryono Putro; Isdawimah Isdawimah; Dewi Yanti Liliana (Green Publisher Indonesia, 2025)
Mardha Haryono Putro. Master's Program in Applied Electrical Engineering. Online Monitoring System for Harmonic Filters in a Three-Phase Inverter with a Capacity of 110 kW. This study aims to design and implement an Internet of Things (IoT)-based electrical power quality monitoring system and to design a single-tuned passive harmonic filter to reduce the fifth-order individual harmonic distortion (iHD-5) in a 110 kW three-phase inverter system. The monitoring system was developed using a GAE MG50 power meter and an ESP8266 microcontroller, integrated with Google Sheets and the Blynk app for real-time monitoring. Data was collected over 7 days before and after filter installation. Measurement results showed an initial THDi value of 67.35% and a fifth-order iHD value of 47.8%, exceeding the 12% threshold according to IEEE Std 519-1992. The passive filter was designed with a capacitance of 155.2 µF and an inductance of 2.89 mH. After installation, THDi decreased to 38%, iHD-5 to 9.96%, neutral current dropped from 18 A to 9 A, and power factor improved from 0.76 to 0.91. Energy savings are estimated at ± 2,484 kWh per month, equivalent to ± Rp 2,571,391 at an industrial electricity rate of Rp 1,035.78/kWh. The research results indicate that integrating an IoT monitoring system with a passive harmonic filter can improve energy efficiency, reduce harmonic distortion, and enhance power quality in industrial electrical systems.